Biomining and methanogenesis for resource extraction from asteroids. (November 2015) - Klas, Michael; Tsafnat, Naomi; Dennerley, Joel; Beckmann, Sabrina; Osborne, Barnaby; Dempster, Andrew G.; Manefield, Mike
Abstract: Biotechnological resource extraction methods such as biomining and biogas production could fill a vital niche in currently proposed ways for extracting minerals and producing fuel on asteroids. Well established on Earth, biomining applications on asteroids could significantly increase the output and efficiency of minerals processing. Biogas production, unlike conventional fuel extraction processes, relies on the presence of carbonaceous chondrite on asteroids. Bacteria placed on or within the asteroid would ferment these carbon sources and methanogenic Archaea would produce methane for spacecraft propulsion and industrial applications. Supporting microbial communities in space requires a thorough understanding of the limitations of microbial life, interacting environmental parameters as well as factors such as asteroid structure and nutrient availability. This paper examines engineering and ecological principles required to support an asteroid based microbial community. In addition socioeconomic factors such as current space policy and potential economic prospects are also discussed. Biotechnology is increasingly filling a niche in conventional engineering; with the advent of a new era in space, evolving these technologies is vital to fully developing humanity's space faring capabilities.